Achromobacter xylosoxidans (Alcaligenes xylosoxidans subsp. xylosoxidans) bacteremia associated with a well-water source: case report and review of the literature. - Spear, J B (1988)
A case of community-acquired Achromobacter xylosoxidans bacteremia in a patient with metastatic breast carcinoma is described. The patient's home drinking water was identified as the source of her bacteremia. The case represents the first in which a community-acquired infection due to this organism has been attributed to a documented water source.